IMPLEMENTING TWO STAY TWO STRAY MODEL ON LOW MOTIVATED STUDENTS’ CLASSROOM ACTIVE LEARNING - Mohamad Akbar Ardiansyah (Journal of English Education Program (JEEP), 2020)
This paper reports about the implementation of Two Stay Two Stray model on low motivated students' classroom active learning in one of Islamic senior high school, Ciamis. This study focused on the implementation of Two Stay Two Stray model as a teacher strategy in involving students during English learning in the classroom. The purpose of this research were to find out the teacher’s strategy in involving the students by using Cooperative learning of model Two Stay Two Stray, and low motivated students’ perception about the strategies used by the teacher in involving them during English learning activities in class. A case study methodology was used in this research. This research took one class of the tenth grade as the participant, and data were collected trough classroom observation and questionnaire. The findings of this research revealed that the implementation of the Two Stay Two Stray learning model as a teaching strategy is able to involve students in English learning process in the classroom. Cooperative learning of model Two Stay Two Stray is effective to be applied in teaching and learning English in the classroom. Finally, the author provides suggestions of how this model can be an alternative technique for teachers to teach speaking, writing, listening, and reading.Keywords: Two Stay Two Stray (TS - TS) model, Teacher Strategies, Motivation, Active Learning.